2013
DOI: 10.1631/jzus.a1300210
|View full text |Cite
|
Sign up to set email alerts
|

A new energy harvester using a piezoelectric and suspension electromagnetic mechanism

Abstract: Abstract:This study presents a new design of a piezoelectric-electromagnetic energy harvester to enlarge the frequency bandwidth and obtain a larger energy output. This harvester consists of a primary piezoelectric energy harvesting device, in which a suspension electromagnetic component is added. A coupling mathematical model of the two independent energy harvesting techniques was established. Numerical results show that the piezoelectric-electromagnetic energy harvester has three times the bandwidth and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…The first and the second resonances of such device were 20 Hz and 300 Hz. Wang et al [32] and Shan et al [33] analyzed the characteristics of the two degree-of-freedom (2DOF) HEH. Among these works, the resonant frequencies of VEHs are fixed when the prototypes are assembled.…”
Section: Introductionmentioning
confidence: 99%
“…The first and the second resonances of such device were 20 Hz and 300 Hz. Wang et al [32] and Shan et al [33] analyzed the characteristics of the two degree-of-freedom (2DOF) HEH. Among these works, the resonant frequencies of VEHs are fixed when the prototypes are assembled.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Recently, researchers found that the energy of the suspension vibration can be regenerated by means of magnetic suspension [5][6][7][8][9][10][11] and piezoelectric suspension. [12][13][14][15][16] In Segal and Lu, 17 the influence of suspension damping, tires, and road surface roughness on the vehicle running resistance was analyzed, and it was noted that, when the vehicle drove at a speed of 48 km/h, the damper dissipated approximately 200 W of energy. Hsu 18 deeply studied the active suspension based on the Linear-Quadratic-Gaussian (LQG) control strategy, and it was found that, when the vehicle was driving at a high speed of 96 km/h, the vibration energy can be regenerated by 400 J. Yu et al 19 analyzed the feasibility of the active energy-regenerative suspension, and the simulation results showed that, when the vehicle drove at 20 m/s on a C level road for 20 s, the energy dissipated by the passive suspension was 651 kJ.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays a number of informative studies and developments have been presented in this area [15][16][17]. Most reported references have investigated hybrid PE and EM energy harvesters through numerical analysis, finite element simulation and experimental methods [18][19][20][21][22]. Only a few researchers have established mathematical models for hybrid PE and EM energy harvester designs [23][24][25].…”
Section: Introductionmentioning
confidence: 99%